ANALISIS RANCANGAN E-BUSINESS UNTUK PENGEMBANGAN UMKM DI KEPULAUAN BANGKA BELITUNG (STUDI KASUS PRODUK UNGGULAN SARI JERUK KUNCI, KOPERASI PRODUSEN MELATI MAJU BERSAMA PANGKALPINANG) - Inawati; Ruben Manullang, Rizal; Zamhari (STIE IBEK Pangkalpinang, 2021)
This research was entitled: “Analisis Rancangan E-Business Untuk Pengembangan UMKM Di Kepulauan Bangka Belitung; Studi Kasus Produk Unggulan Sari Jeruk Kunci, Koperasi Produsen Melati Maju Bersama Pangkalpinang”. The background of this research is based on the necessity for the company to have an online operational platform. The purposes of this study were to plan systematically regarding the Melati Maju Bersama Producer Cooperative in achieving organizational goals that are effective and efficient, to carry out the implementation related to what has been planned so that the Melati Maju Bersama Producer Cooperative achieves the organizational goals set, effective and efficient, and to carry out supervision in the Cooperative Producers of Melati Maju Bersama in order to achieve organizational goals that are effective and efficient. The method of research is a descriptive qualitative The method used in this study is descriptive with a qualitative approach with the aim of describing and describing existing phenomena, both natural and human engineered, which pays more attention to the characteristics, quality, and interrelationships between activities. The theories and methods used in this research are the theory of Management, Marketing Management, Consumer Behavior, Marketing Strategy, Management Information System, E-Marketing, Affiliate Marketing, E-Business, E-Commerce, and the Unified Process Rational Methodology (RUP) and PIECE Analysis. The results of the study prove that: (1) the process of identifying a systematic plan for the Melati Maju Bersama Producer Cooperative in order to improve organizational goals effectively and efficiently is carried out by building / creating a domain or service center that is integrated with the internet., (2) Jasmine Producers Cooperative Maju Bersama in carrying out the implementation process in order to improve organizational goals that are effective and efficient in maximizing the use of hardware, software and brainware., (3) Supervision that occurs in the Melati Maju Bersama Producer Cooperative in order to improve organizational goals that are effective and efficient.